Foreclosing on a Loan Agreement cum Deed of Assignment: A Review of the Federal Court Decision in Damai Freight v Affin Bank Berhad - Goh, Mark (Journal of Malaysian and Comparative Law, 2019)
I. INTRODUCTION The Federal Court in Damai Freight v Affin Bank Berhad1 (Damai Freight) had finally resolved the conundrum surrounding situations where the Issue Document of Title (commonly known as the ‘title’) of a property is issued but is not transferred to the assignor whilst the lender is foreclosing a property secured by a Loan Agreement cum Deed of Assignment (LADA). A lender (usually the bank) may face various legal challenges which may affect the legality of its foreclosure proceeding if the title is issued before the lender completes the foreclosure under a LADA.2 Should the bank complete its foreclosure under the LADA, despite the issuance of the title? Will the bank be in breach of the National Land Code (NLC) if it proceeds to foreclose under the original LADA If the bank decides to adopt the safer route of registering the Charge and recommencing foreclosure proceedings under the NLC, it would have lost valuable time, money and effort in its original foreclosure proceedings under the LADA. Alternatively, if the bank chooses not to register the Charge, it runs the risk of the court declaring the entire foreclosure proceedings void once the assigned property is issued with a title.